2014
DOI: 10.1016/j.resuscitation.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Debriefing bystanders of out-of-hospital cardiac arrest is valuable

Abstract: Debriefing by emergency medical dispatchers to OHCA bystanders stimulates reflection, positively influencing the ability to cope with the emotional reactions and the cognitive perception of own performance and motivates improvement of CPR skills. Importantly, it increases confidence to provide CPR in the future. Implementation of telephone debriefing to bystanders at Emergency Medical Dispatch Centres is a low complexity and a low cost intervention though the logistic challenges have to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 24 publications
1
65
0
Order By: Relevance
“…Others mainly studied PTSD in family members of OHCA patients [16][17][18][19], or reported on bystanders' psychological reactions [7,8] and the importance of debriefing bystanders [20]. Axelsson et al [8] found two independent factors positively associated with bystanders' psychological reactions, namely victim outcome and debriefing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others mainly studied PTSD in family members of OHCA patients [16][17][18][19], or reported on bystanders' psychological reactions [7,8] and the importance of debriefing bystanders [20]. Axelsson et al [8] found two independent factors positively associated with bystanders' psychological reactions, namely victim outcome and debriefing.…”
Section: Discussionmentioning
confidence: 99%
“…Axelsson et al [8] found two independent factors positively associated with bystanders' psychological reactions, namely victim outcome and debriefing. Additionally, Møller et al [20] reported that formally debriefing bystanders positively influences the ability to cope with emotional reactions. In our study, almost all lay rescuers talked to at least one person about their experience; only 19 (10%) also spoke to a professional.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the research links knowledge of first-aid techniques to an increased confidence in skills and reduced fears of hurting the person being assisted (Axelsson, Herlitz, and Fridlund, 2000;Mathiesen et al, 2017). Other studies suggest that teamwork-either with other bystanders or an emergency dispatcherand the support provided by others are keys to boosting public confidence in their first-aid skills (Moller et al, 2014;Hansen et al, 2017).…”
Section: Competence and Confidencementioning
confidence: 99%
“…The reviewed literature identifies several barriers relating to the disparity between the sensory environment of the training classroom setting and a real emergency (Moller et al, 2014;Mathiesen et al, 2017). For example, seeing a dying victim can lead to feelings of helplessness or powerlessness with respect to whether the provision of first aid will help (Axelsson, Herlitz, and Fridlund, 2000;Axelsson, 2001;Hansen et al, 2017;Mathiesen et al, 2017).…”
Section: Situational Features Of Emergenciesmentioning
confidence: 99%
“…The success of methods used to train the general public in CPR and AED use have been assessed through simulation, and with surveys used to examine the likelihood with which an individual would attempt CPR, or use an AED . However, little is known as to how laypeople perceive OHCAs (including CPR and using an AED), given that these data are extremely scarce . Impediments to initiating CPR include panic, and a fear of causing harm or not performing CPR adequately, even for those who have received CPR training or have performed CPR .…”
Section: Introductionmentioning
confidence: 99%